IN-VITRO DIGESTIBILITTY OF BARLEY GRAINS TREATED WITH UREA: IN-VITRO STUDY - & et al., Tawfeeq (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted in a central laboratory of Agriculture College University of Baghdad, to study the effect of treated barley grains with urea as 1: 1 urea: barley grain (w:w) with or without heating on the in-vitro digestibility, total nitrogen content and releasing urea, the results showed a high significant increases (P<0.01) in total nitrogen content of treated barley grains with urea compared with non-treated, where it was 14.77% for barley soaked 24 hours with urea and 17.18% for barley- urea treated with heat and pressure in compared to 2.15% for untreated barley grains. There were continuity in urea production from barley grains soaked with urea for most times 0, 10, 20, 30, 60,120,180, and 240 minutes and a highly significant (P<0.01) compared to barley grains treated with urea. There were no significant differences in the in-vitro digestibility for concentrated rations when substituted treated barley grains with soya bean meal. In conclusion: we can use barley grains soaked with urea for ruminant feeding without side effects in contrast direct feeding of urea.